BANK UMUM SYARIAH: TINGKAT KESEHATAN DENGAN METODE RGEC - Despileny, Iren; Huda, Nurul; Nurnasrina, Nurnasrina; Bte Salman, Nola Fibriyani (Ikatan Sarjana Ekonomi Indonesia Cabang Pekanbaru, 2024)
The purpose of this research is to see the health level of Islamic commercial banks in Indonesia from 2020-2023 with the RGEC (Risk profile, Good Corporate Governance, Earning, Capital) approach. The analysis method used in this research is to use qualitative descriptive analysis, which is a method that aims to describe the state of the company based on the reality that actually occurs in a company. The results of the research Risk Level (Risk Profile): Islamic commercial banks have a low level of risk, with an average risk score of 75.75. This reflects the bank's ability to manage credit, market, operational, and liquidity risks well, maintaining operational stability and sustainability. Good Corporate Governance (GCG): Corporate governance is rated good, with an average score of 1.82. This indicates the application of the principles of transparency, accountability, responsibility, independence, and fairness that support investor and customer confidence. Quality of Earnings: The bank's profitability is at a very adequate level, with an average earning score of 1.68. The bank is able to optimize revenues and manage costs efficiently to achieve stable profits. Capital: Capital levels are highly adequate, with an average capital score of 24.74. This indicates the bank's financial strength to support growth and bear potential risks. This assessment illustrates financial stability, effective risk management, solid governance, and the ability to maintain profitability growth Keywords: